Shoulder internal and external rotations torque steadiness in overhead athletes with and without impingement symptoms - Zanca, G. G.; Saccol, M. F.; Oliveira, A. B.; Mattiello, S. M. (Journal of Science and Medicine in Sport, 2013)
Objectives: This study aimed to investigate torque steadiness of shoulder internal and external rotations in regularly training overhead athletes with and without impingement symptoms. Design: Cross-sectional laboratory study. Methods: Three groups were evaluated: athletes with impingement symptoms (n = 21), asymptomatic athletes (n = 25) and non-athletes (n = 21). To assess torque steadiness, the participants performed 3 submaximal contractions (35% of peak torque) for 10 s each, with the arm at 90° of shoulder abduction and 90° of external rotation. The standard deviation, coefficient of variation, mean exerted torque and time to stability were measured from the steadiness trials. Results: The standard deviation of internal rotation was higher in asymptomatic athletes than in non-athletes (p < 0.01); however, there was no difference between the athletes with impingement symptoms and the other groups. The other variables presented no differences among the groups. Conclusions: Higher torque fluctuation of shoulder internal rotation in asymptomatic athletes may point to neuromuscular adaptations related to throwing training. However, the steadiness patterns of athletes with impingement symptoms did not differ from those of asymptomatic athletes or non-athletes.